2022
DOI: 10.3390/ijerph19074077
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Neuromuscular Deficits in Movement Pattern among Uninjured Federated Youth Basketball Players: A Cross-Sectional Study

Abstract: (1) Background: The aim of the present study was to evaluate and to detect neuromuscular deficiencies in static and dynamic tests among federated youth basketball players. (2) Methods: Cross-sectional study with 778 basketball players. Specific tests and trials were conducted to evaluate members of teams from several clubs in male and female from under 12 (U12) to under 17 (U17) categories. The evaluations consisted of static physical measurements and dynamic measurements. (3) Results: 575 players were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
1
1
0
1
Order By: Relevance
“…The authors identified, among other factors, the difference between the circumferences of the left and right thighs, while in our study, no correlations emerged for the left lower limb, and the difference in the strength of the anterior and posterior thigh muscles, which cannot be evaluated with the method we used [ 27 ]. The lack of evidence for the left lower limb could also be re-evaluated in light of the lack of differences found by Adillón et al [ 26 ] in the stability found between dominant and non-dominant limbs, in accordance with what was previously observed in other studies [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The authors identified, among other factors, the difference between the circumferences of the left and right thighs, while in our study, no correlations emerged for the left lower limb, and the difference in the strength of the anterior and posterior thigh muscles, which cannot be evaluated with the method we used [ 27 ]. The lack of evidence for the left lower limb could also be re-evaluated in light of the lack of differences found by Adillón et al [ 26 ] in the stability found between dominant and non-dominant limbs, in accordance with what was previously observed in other studies [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 83%
“…In partial confirmation of this observation, analyzing neuromuscular movement deficits in 575 young basketball athletes, Adillón et al reported how the main deficiencies are related to postural and dynamic instability of the lower limb joints, combined with deficits in the jumping/landing technique [ 26 ]. More difficult to interpret, and probably in partial contrast, is what Wang and Baek found in the development of a reduction algorithm for early identification of the risk of injuries in basketball.…”
Section: Discussionmentioning
confidence: 92%
“…21 Pemain dengan usia muda dapat mempengaruhi derajat knee valgus yang lebih buruk saat bermain, hal ini menunjukkan bahwa keseimbangan yang dimiliki masih dalam fase perkembangan. 22 Dalam penelitian tidak di temukan perbedaan yang signifikan antara pemain dengan intensitas latihan tinggi dan sedang. Hal ini berbeda dengan pembahasan yang menyebutkan semakin tinggi intensitas pemain, maka semakin tinggi juga risiko terkena cedera.…”
Section: Diskusi Karakteristik Respondenunclassified